INDONESIAN EFL TEACHER'S LIVED EXPERIENCES IN ONLINE TEACHING AMIDST THE COVID-19 PANDEMIC - Hatmi Asminoto (Language-Edu, 2021)
ABSTRACTCorona virus was first discovered in Wuhan, China, in 2019. This virus is spreading very quickly to the various countries of the world, and to make all the elements of life find obstacles in social mobility, economy and education. Therefore, WHO then took a stand to declare the spread of this virus to be a pandemic for entire countries. In the context of education in Indonesia, the government has issued various policies to tackle the spread of this virus by closing all formal educational institutions. The offer given by the government from this closure is an online learning method during the corona virus pandemic. The focus of this researvh is to investigate how the online learning process during a pandemic, how the influence of teachers on students when learning onlineThe researcher of this study is conducting by using qualitative descriptive research. The research belongs to descriptive qualitative design because it is intended to find out how is teacher’s perception of online English learning in the Covid-19 pandemic at secondary school. To collect the data, the researcher used online interview. The subjects of the study were 5 teachers who teaches at the secondary schools. They have been teaching English for 2-5 years and the participants was chosen because during this pandemic all teachers are teaching online.The results showed of teacher interviews that all respondents give good and bad lived experiences about teaching online learning. They claim that they can improve their learning system and get new experiences from the media used in online learning. On the other hand, the teacher also gave the perception that online learning has obstacles, there are bad networks, inadequate facilities, inadequate quality of mobile phones, minimalist quotas and applications used in online learning. However, teachers must continue to apply online learning or distance learning in the midst of the COVID-19 pandemic. For future researchers who wish to conduct similar study can use this research as a reference which is not only focuses on the teachers' lived experience and perceptions but also student perceptions with different participants.Keywords: Online Learning, COVID-19, English Language Teaching